Simvastatin combined with bone marrow mesenchymal stromal cells (BMSCs) improve burn wound healing by ameliorating angiogenesis through SDF-1α/CXCR4 pathway - Javad Mohajer Ansari; Parisa Ramhormozi; Ronak Shabani; Hamidreza Pazoki-toroudi; Abazar Yari; Mahmood Barati; Mostafa Dahmardehei; Azar Babakhani; Maliheh Nobakht (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Chemokines are wound mediators that promote angiogenesis during wound healing. We hypothesized that Simvastatin in combination with the bone marrow mesenchymal stromal cells (BMSCs) improve burn wound healing by ameliorating angiogenesis via SDF-1α/CXCR4 pathway. Materials and Methods: Under general anesthesia, deep partial-thickness burns were created on the inter-scapular area of 48 male rats. Study groups were administrated with petroleum jelly (Simvastatin Vehicle), a single dose of intradermal BMSCs (1×106), topical Simvastatin (0.5 mg/kg) daily and combination of BMSCs and Simvastatin for 14 days. In this study, we used MTT assay, in vivo and in vitro wound closure, H&E and Trichorome staining, immunohistochemistry (IHC), real- time PCR, Western blot and tube formation assay. Results: A significant improvement in wound closure percentage, epithelial thickness, collagen remodeling, and up-regulation of stromal cell-derived factor 1 alpha (SDF1α), C-X-C chemokine receptor type 4 (CXCR4), protein kinase B (AKT), and phosphatidylinositol 3- kinase (PI3K), as well as CD31 and vascular endothelial growth factor (VEGF) expression were observed after treatment with simvastatin, BMSCs and combination of them compared to the vehicle group. However, the co-treatment group revealed considerable superiority in examined factors. BMSCs treated with Simvastatin showed the highest viability in the concentration of 0.5 and 1 Nanomolar (nM). Increment in proliferation and capillary vessels formation of BMSCs was observed in the 0.5 nM and 1 nM concentrations of Simvastatin in vitro. Conclusion: Treatment of deep partial-thickness of burns with co-treatment of BMSCs and Simvastatin resulted in improved burn wound healing through up-regulating of SDF-1α/CXCR4 pathway.